Cytoplasmic 5′-3′ exonuclease Xrn1p is also a genome-wide transcription factor in yeast - Medina, Daniel A.; Jordán-Pla, Antonio; Millán-Zambrano, Gonzalo; Chávez, Sebastián; Choder, Mordechai; Pérez-Ortín, José E. (Frontiers in Genetics, 2014)
The 5’ to 3’ exoribonuclease Xrn1 is a large protein involved in cytoplasmatic mRNA degradation as a critical component of the major decaysome. Its deletion in the yeast Saccharomyces cerevisiae is not lethal, but it has multiple physiological effects. In a previous study, our group showed that deletion of all tested components of the yeast major decaysome, including XRN1, results in a decrease in the synthetic rate and an increase in half-life of most mRNAs in a compensatory manner. Furthermore, the same study showed that the all tested decaysome components are also nuclear proteins that bind to the 5’ region of a number of genes. In the present work, we show that disruption of Xrn1 activity preferentially affects both the synthesis and decay of a distinct subpopulation of mRNAs. The most affected mRNAs are the transcripts of the highly transcribed genes, mainly those encoding ribosome biogenesis and translation factors. Previously, we proposed that synthegradases play a key role in regulating both mRNA synthesis and degradation. Evidently, Xrn1 functions as a synthegradase, whose selectivity might help coordinating the expression of the protein synthetic machinery. We propose to name the most affected genes “Xrn1 synthegradon”.